2017
DOI: 10.1016/j.biortech.2017.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biochemical composition during hydrothermal liquefaction of algae on product yields and fuel properties

Abstract: Hydrothermal liquefaction (HTL) of nine algae species were performed at two reaction temperatures (280 and 320°C) to compare the effect of their biomass composition on product yields and properties. Results obtained after HTL indicate large variations in terms of bio-oil yields and its properties. The maximum bio-oil yield (66wt%) was obtained at 320°C with a high lipid containing algae Nannochloropsis. The higher heating value of bio-oils ranged from 31 to 36MJ/kg and around 50% of the bio-oils was in the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…Moreover, the energy recovery corroborates with biocrude yields. In this study, ER were 71% for M1, 67% for M2, 75% for M3, 89% for M4 and 86% for M5 and were within the range of reported scientific literature [3,5,27]. Skakya et al, [5] reported ER of 47% for Chlorella sp., 78% for Scenedesmus sp.…”
Section: Effect Of Separation Protocols On Energy Densitysupporting
confidence: 54%
See 3 more Smart Citations
“…Moreover, the energy recovery corroborates with biocrude yields. In this study, ER were 71% for M1, 67% for M2, 75% for M3, 89% for M4 and 86% for M5 and were within the range of reported scientific literature [3,5,27]. Skakya et al, [5] reported ER of 47% for Chlorella sp., 78% for Scenedesmus sp.…”
Section: Effect Of Separation Protocols On Energy Densitysupporting
confidence: 54%
“…The higher heating value (HHV), chemical energy recovered in biocrude, and the hydrogen-to-carbon ratio were determined in accordance to methods explained previously [20,24]. Sample of biocrudes (diluted to 2.5v/v% with acetone) were analysed with Gas Chromatography-Mass Spectrometer (GC-MS) (Agilent Technologies 6890 N, equipped with Agilent HP-5 capillary column of 50m×200µm×0.33µm) in accordance to the method reported previously [5,16].…”
Section: Product Yields and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In typical liquefaction, the biomass feedstock is decomposed into different product fractions, such as aqueous phase, biocrude, gaseous phase, and the solid residue . The biocrude is a complex mixture of organic compounds, including oxygen and nitrogen‐containing compounds, esters, hydrocarbons, and organic acids . So far, the biocrude is thought to be a promising substitution of fossil fuel due to its high overall heating values and renewable characteristics.…”
Section: Introductionmentioning
confidence: 99%